Indexicals and Reference-Shifting: Towards a Pragmatic Approach. - Åkerman, Jonas (Philosophy & Phenomenological Research, 2017)
I propose a pragmatic approach to the kind of reference-shifting occurring in indexicals as used in e.g. written notes and answering machine messages. I proceed in two steps. First, I prepare the ground by showing that the arguments against such a pragmatic approach raised in the recent literature fail. Second, I take a first few steps towards implementing this approach, by sketching a pragmatic theory of reference-shifting, and showing how it can handle cases of the relevant kind. While the immediate scope of the paper is restricted to indexicals and reference-shifting, and the discussion is confined to a specific range of theories and cases, the approach proposed is compatible with a fairly broad range of more or less semantically conservative theories, and many of the conclusions drawn are significant for the evaluation of pragmatic explanations in philosophy more generally. The overall goal is to offer a new perspective on the issues under discussion, and to prompt philosophers to reconsider some of the established methods by which pragmatic explanations are evaluated.